2010
DOI: 10.1155/2011/434378
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Amplitude Modulation Synthesis

Abstract: A recently rediscovered sound synthesis method, which is based on feedback amplitude modulation (FBAM), is investigated. The FBAM system is interpreted as a periodically linear time-varying digital filter, and its stability, aliasing, and scaling properties are considered. Several novel variations of the basic system are derived and analyzed. Separation of the input and the modulation signals in FBAM structures is proposed which helps to create modular sound synthesis and digital audio effects applications. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Constructing the knowledge of the environment is done by manipulating and directly interacting with the concepts and objects: not only the software environment, but also the block diagrams, literature, and sketches that "surround and embellish the code" (Noss and Clayson 2015). For example, as students independently implemented synthesis with feedback amplitude modulation (Kleimola et al 2011), a series of creative answers emerged from building, reflecting, and debugging as a process of "knowledge appropriation" (Papert 1980).…”
Section: Recreate and Transcribementioning
confidence: 99%
“…Constructing the knowledge of the environment is done by manipulating and directly interacting with the concepts and objects: not only the software environment, but also the block diagrams, literature, and sketches that "surround and embellish the code" (Noss and Clayson 2015). For example, as students independently implemented synthesis with feedback amplitude modulation (Kleimola et al 2011), a series of creative answers emerged from building, reflecting, and debugging as a process of "knowledge appropriation" (Papert 1980).…”
Section: Recreate and Transcribementioning
confidence: 99%
“…Arbitrary switching of filters was discussed in Laroche (2007), where a framework for the analysis of difficult cases was provided. More practical uses were also discussed, such as the use of coefficient modulation by periodic signals (Kleimola et al, 2011;Lazzarini et al, 2009Lazzarini et al, , 2011Timoney et al, 2014), building on the recent theory of periodic linear time-varying (PLTV) filters (Cherniakov, 2003), for both finite and infinite response cases. Following this, a special case of arbitrary time-varying linear finite impulse response filters (TVFIR) was introduced for time-varying convolution applications (Brandtsegg et al, 2018), which is the focus of the discussion in this paper.…”
Section: Time-varying Convolutionmentioning
confidence: 99%
“…In particular, some significant attention has been dedicated to infinite impulse response types that whose coefficients are modulated by a periodic signals [39][40][41][42]. These filters tend to be of lower order (first or second order), which have equivalent longer forms made up of two sections arranged in series, a TVFIR and a fixed-coefficient IIR [41]. It has also been shown that the most significant part of the effect of these filters is contained in the TVFIR component.…”
Section: Time-varying Convolutionmentioning
confidence: 99%